Arterial Stiffness in Kidney Transplant Recipients: an Overview of Methodology and Applications - Khoshdel, Ali Reza; Carney, Shane L (Urology Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-language:FA; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Introduction: Cardiovascular disease is still a major cause of mortality in kidney transplant patients. This is partially attributed to the nonclassic cardiovascular risk factors including arterial stiffness, an established independent predictor of mortality in several patient populations. Materials and Methods: An extensive search was performed to review the evolution process of the method for arterial stiffness assessment and sphygmology and their applications in chronic kidney disease before and after kidney transplantation. Results: Despite a marked change in methodology from the ancient medical practice to the current modern medicine, noninvasive assessment of arterial stiffness is still based on pulse analysis. Currently, pulse wave velocity, augmentation index, and pulse wave reflection are preferred indexes for arterial stiffness. Increased arterial stiffness has been reported in diabetes mellitus, hypertension, chronic kidney disease, cardiovascular disease, and elderly, and reduction of arterial stiffness is a key element for efficacy of the treatment and mortality reduction. Conclusion: Noninvasive assessment of arterial stiffness is suggested as a part of clinical assessment for kidney transplant recipients and donors and facilitates defining high-risk patients for development of cardiovascular disease. A combination of techniques is recommended for this purpose.